2016
DOI: 10.6106/jcepm.2016.6.2.008
|View full text |Cite
|
Sign up to set email alerts
|

Critical Barriers to the Practice of Effective Cost Planning in the Ghanaian Construction Industry

Abstract: Cost planning practices in the construction industry worldwide has gained much popularity in recent times due to economic recession and stringent measures that various procurement laws prescribe in most developed and developing countries. Nevertheless, these practices in developing countries such as Ghana are constrained with the existence of critical barriers that render them non-effective and hence, accounting for the numerous abandonment of both private and public projects. Consequently, this study was enun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Currently, project managers in the road infrastructure sector originate from civil engineering, materials engineering, quantity surveying, geomatic surveying and others (Kissi et al , 2014). Though project management concepts and practices have been globally acclaimed over the past seven decades, the road construction industry in Ghana started over four decades ago (Ahadzie and Amoah-Mensah, 2010).…”
Section: Project Management Practices In the Road Infrastructure Sectormentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, project managers in the road infrastructure sector originate from civil engineering, materials engineering, quantity surveying, geomatic surveying and others (Kissi et al , 2014). Though project management concepts and practices have been globally acclaimed over the past seven decades, the road construction industry in Ghana started over four decades ago (Ahadzie and Amoah-Mensah, 2010).…”
Section: Project Management Practices In the Road Infrastructure Sectormentioning
confidence: 99%
“…As the demand for improved and efficient road infrastructure projects in developing countries keeps rising, project managers must position themselves toward best practices to meet the growing infrastructure demands and challenges. In Ghana, project management professionals face a myriad of technical and nontechnical project management challenges, including little documentation on project management best practices, funding and its conditionalities (Kissi et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quartey and Afful-Mensah [33] also concluded that the Ghanaian economy is faced with huge interest rate, double inflation figures, and high taxes, making it difficult for small, medium, and large scale construction firms to access funding for projects. The highly unstable economic parameters and high inflationary trends contribute to project cost overruns, inaccuracies, and unreliability of cost management practices [34]. An assessment of GET-Fund projects in Ghana revealed that only 2 out of 10 projects in Ashanti Region were completed within project budget [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…An assessment of GET-Fund projects in Ghana revealed that only 2 out of 10 projects in Ashanti Region were completed within project budget [33]. In an attempt to minimize the impact of economic factors influencing cost of buildings, [34][35][36] developed a Framework for the computation of construction cost indices using rate, but previous work by Asumadu-Yeboah [37] concluded that the contractors were not satisfied with the level of compensation and that the indices have not been consistent to the unstable economic conditions in Ghana. Kissi et al [38] also considered the need to develop Tender Price Index to predict estimate for tender in the Ghanaian building industry with the aim of improving the level of accuracy and reliability of early design estimate.…”
Section: Literature Reviewmentioning
confidence: 99%